Heidegger's Pragmatism : Understanding, Being, and the Critique of Metaphysics - Okrent, Mark (Cornell University Press, 2019)
Heidegger's Pragmatism deals with the relation between Martin Heidegger's early analysis of intentionality and his eventual rejection of metaphysics. Arguing for the essentially pragmatic nature of the early Heidegger's discussion of understanding, Mark Okrent shows that Heidegger's subsequent critique of metaphysics follows directly from his long-held pragmatic understanding of intentionality.Heidegger's Pragmatism is written with a clarity that makes it accessible to analytic and continental philosophers alike. Its boldly original conclusions will engage Heidegger scholars, literary theorists, intellectual historians, and a wide range of philosophers.